Natural rubber latex biodevice as controlled release system for chronic wounds healing - De Barros, Natan Roberto [UNESP]; Heredia-Vieira, Silvia Cristina [UNESP]; Borges, Felipe Azevedo [UNESP]; Benites, Nikollas Moreira [UNESP]; Dos Reis, Camila Eugênia [UNESP]; Miranda, Matheus Carlos Romeiro [UNESP]; Cardoso, Claudia Andrea Lima; Herculano, Rondinelli Donizetti [UNESP] (IOP Publishing, 2018)
The chronic wounds problem affect millions of people worldwide, becoming a great challenge to the healthcare systems. The normal healing consists of three phases: Inflammation, proliferation and remodelation. Problems in any of these can lead to chronic wounds. The disease diabetes, for example, induces systemic production of free radicals, and also the antioxidant capacity decreases, which induces severe tissue damage decreasing the healing process. The diabetic disease state can also disrupt the balance between promoting vessel growth and proliferation and promoting vessel maturation and quiescence. The idea was to develop an antioxidant extract loaded matrix and evaluate the in vitro released antioxidant activity by the comparison between two spectrometric techniques to obtain a model dressing that could provide the biological advantages of both starting materials, increased vascularization for the natural latex matrix, and antioxidant activity for the S. marginata extract. According to FTIR analysis, matrix and extract did not interact chemically. Furthermore, at 67 h, up to 27% of all incorporated extract was released. The SEM images showed a portion of extract on the matrix surface, being responsible for the burst release. On the other hand, another portion remains within the matrix, being responsible for the slower release. The extract antioxidant activity was maintained even after its incorporation into the matrix. The comparison between the results obtained showed that the fact that the DPPH EPR spectrum has a relatively simple signal due only to the free radical is an advantage in relation to the optical spectroscopy. Based on the obtained results, it was possible to conclude that matrix is able to load the extract and maintain its antioxidant activity. However, in vivo and clinical assays are needed in the future to prove the clinical efficiency of the developed dressing.
Keywords: antioxidant activity; biomaterial; Natural rubber latex; S. marginata; wound healing